Performance evaluation of various 2-d laser scanners for mobile robot map building and localization - Lim, Thol Yong (UTEM, 2016)
A study has been carried out to investigate the performance of various 2 - D laser scanners , which influ ence the map building quality and localization performance for a mobile robot. Laser scanners are increasingly used in auto mation and robotic applications. T hey are widely used as sensing devices for map building and localization in navigation of mobile ro bot. Laser scanners are commercially available, but there is very little published information on the performance comparison of various laser scanners on the mobile robot map building and localization. Hence, this work studies the performance by comparing four laser scanners which are Hokuyo URG04LX - UG01, Hokuyo UTM30LX, SICK TIM551 and Pepperl Fuchs ODM30M. The results, which are verified by comparison with the reference experimental data, indicated that the angle resolution and sensing range of laser scan ner are key factors affecting the map building quality and position estimation for localization. From the experiment, laser scanner with 0.25° angle resolution is optimum enough for building a map of sufficient quality for good localization performance . W i th 30meter of sensing range, a laser scanner can also result in better localization performance , especially in big environment.